Amphotericin B severely affects expression and activity of the endothelial constitutive nitric oxide synthase involving altered mRNA stability - Suschek, Christoph Viktor (2000)
1. The therapeutic use of the antifungal drug amphotericin B (AmB) is limited due to severe side effects like glomerular vasoconstriction and risk of renal failure during AmB administration. As nitric oxide (NO) has substantial functions in renal autoregulation, we have determined the effects of AmB on endothelial constitutive NO synthase (ecNOS) expression and activity in human and rat endothelial cell cultures. 2. AmB used at concentrations of 0.6 to 1.25 μg ml(−1) led to increases in ecNOS mRNA and protein expression as well as NO production. This was the result of an increased ecNOS mRNA half-life. In contrast, incubation of cells with higher albeit subtoxic concentrations of AmB (2.5–5.0 μg ml(−1)) resulted in a decrease or respectively in completely abolished ecNOS mRNA and protein expression with a strongly reduced or inhibited ecNOS activity, due to a decrease of ecNOS mRNA half-life. None of the AmB concentrations affected promoter activity as found with a reporter gene construct stably transfected into ECV304 cells. 3. Thus, our experiments show a concentration-dependent biphasic effect of AmB on expression and activity of ecNOS, an effect best explained by AmB influencing ecNOS mRNA stability. In view of the known renal accumulation of this drug the results reported here could help to elucidate its renal toxicity.